Peran OHCHR dalam Kasus Pembunuhan di Luar Hukum dalam Kebijakan Perang Melawan Narkoba Filipina - Rakhmawulan, Dinda Anisa; Nuraeni, Nuraeni (Jurnal Hubungan Internasional, 2021)
The Office of the UN High Commissioner of Human Rights is an intergovernmental human rights organization that provides advisory services and technical cooperation at both the national and regional levels. OHCHR will get involved if a country experiences obstacles related to human rights. This paper aims to analyze and describe the role of OHCHR in cases of extrajudicial killings since the enactment of the War on Drugs Policy in the Philippines. The author uses a qualitative approach with descriptive methods. The author obtains the required data through literature studies and interviews. The results showed that OHCHR has several roles in its involvement, namely as an actor to communicate with the government, victims' families, and other international organizations; as a forum to discuss human rights cases in the regular sessions of the UN Human Rights Council; also as a political resource where countries fight over what the OHCHR have to do to support their positions.